Wind Farm Impacts on Birds and Bats: Planning, Baseline Studies, Mitigation and Monitoring Overview - Rodrigo Fernández-Mellado; Eladio L. García de la Morena (Пернатые хищники и их охрана)
Onshore wind energy has undergone enormous development over the last decade globally. Looking only at the European Union (EU), 11 GW were installed in 2021 alone. But the predictions are even higher for the period 2022–2026. If we focus our attention only on the group of 27 EU countries, the average annual installed onshore wind capacity is expected to be 18 GW. In Kazakhstan, wind energy has been installed so far in a small number of projects, although it has enormous capacity for expansion.